2018
DOI: 10.12691/jfnr-6-6-2
|View full text |Cite
|
Sign up to set email alerts
|

The CH<SUB>2</SUB>Cl<SUB>2</SUB><i> </i>Extract Fraction from<i> Ficus erecta</i> var. <i>sieboldii</i> (Miq.) King Suppresses Lipopolysaccharide-mediated Inflammatory Responses in Raw264.7 Cells

Abstract: A phytochemical application of leaves from Ficus erecta var. sieboldii (Miq.) King has not been widely investigated. We determined an anti-inflammatory effect of F. erecta extracts on lipopolysaccharide (LPS)-mediated production through modulation of several pro-inflammatory mediators and prostaglandin E2 (PGE 2). Among the F. erecta extracts, the CH 2 Cl 2 fraction (CFE) most effectively suppressed the LPS-mediated production of nitric oxide (NO) in Raw264.7 cells. As determined by immunoblotting and PCR, CFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For a long time, it has been known to be effective in promoting rejuvenation, bone health, wound recovery, blood circulation, and detoxification [8]. In recent studies, the potential of FES as a functional food was reported by evaluating its catechin content, antioxidant activity, and anti-inflammatory effects in a hypersensitivity-free macrophage model [9,10]. Sasamorpha has been reported to be widely distributed in Asian countries such as Korea, China, and Japan [11].…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, it has been known to be effective in promoting rejuvenation, bone health, wound recovery, blood circulation, and detoxification [8]. In recent studies, the potential of FES as a functional food was reported by evaluating its catechin content, antioxidant activity, and anti-inflammatory effects in a hypersensitivity-free macrophage model [9,10]. Sasamorpha has been reported to be widely distributed in Asian countries such as Korea, China, and Japan [11].…”
Section: Introductionmentioning
confidence: 99%